Emotional Labor And Compassion Fatigue: A Correlational Analysis On Mental Health Practitioners - Khawaja, Sumra Mumtaz; Saeed, Javeria; Naz, Qirat; Zahid, Qammar Vish (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
In this fast-paced world, mental health is at a greater toll due to the continuous pressure of excellence. Emotional labor is common among mental health professionals, and with extended practice, they are more prone to compassion fatigue and job burnout. This study examined the relationship between emotional labor and compassion fatigue among mental health practitioners by considering the demographic factors (age, gender, qualifications, and experience). It employed a cross-sectional design to survey mental health practitioners. The sample (N=117) comprised male (n=50) and female (n=67) aged 24 to 61 years old. Participants were selected from hospitals, rehabilitation centers, and community health centers in collaboration with department administrators. Results showed that emotional labor was positively associated with compassion fatigue (p<0.01). Female professionals exhibited higher emotional labor and compassion fatigue levels than their male counterparts. Mental health professionals with extended job experience exhibit lower levels of emotional labor and compassion fatigue than those with less experience in the mental health field. Moreover, the results indicated that older professionals reported a lower level of emotional labor than those in the younger age group. There needs to be a supportive environment addressing the diverse factors affecting the emotional well-being of these professionals.